EVOLUTION OF THE PRODUCTION FACTORS IN THE ROMANIAN AGRICULTURE AND ITS POTENTIAL FOR A COMPETITIVE DEVELOPMENT IN THE ENLARGED EU - Turtoi, Crina; Camelia, Toma; Camelia, Gavrilescu (Economics of Agriculture, 2018)
The present endowment of the Romanian agriculture with technical means, corroborated with the scarce management at the level of the agricultural holdings, cannot ensure the performance of agricultural works on due time, as provided in the cropping technologies. This results both in a low productivity level and in large harvest losses. The paper is analyzing the trend of the main components of the production factors and the main synthetic indicators quantifying labour productivity in agriculture: (i) agricultural output per employed person and (ii) gross value added per employed person. Among the main causes leading to this situation, the following have been identified: excessive land fragmentation, low scale use of the technical-material base, precarious operation of the irrigation system, inadequate management of the agricultural holdings and of the production factors in general. The study is accompanied by a comparative analysis with the situation in the EU Member States.